Hepatitis E in the Royal Nepal Army and the Kathmandu Valley - Shrestha, Khagendra Bahadur (Medical Journal of Shree Birendra Hospital, 2000)
Hepatitis E in the Royal Nepal Army and the Kathmandu Valley